PEMANFAATAN MEDIA GAME EDUKASI WORDWALL UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATERI ORGAN PERNAPASAN MANUSIA DI KELAS V SDN 060912 MEDAN - Yulia Angreni Siregar; Chairunnisa Amelia (STKIP Subang, 2024)
To be successful in learning, interest in learning is one of the things that needs to be instilled in students. Students in class V at SDN 060912 Medan continue to show high interest in learning. Classroom Action Research (CAR) is intended to create active, innovative and creative learning methods that can increase students' interest in mathematics using wordwall media. PTK is carried out in two cycles, with planning, action, observation and reflection activities included in it. The results of the research show that using the Wordwall educational game can increase students' interest in learning in class V at SDN 060912 Medan, as shown by the increase in the percentage of students fulfilling the learning interest indicators. The results of the analysis of students' interest in learning observation sheets showed an increase in students' interest in learning. In cycle I, the percentage was 78% in the good category and 83.6% in the very good category.